2020
DOI: 10.1097/olq.0000000000001129
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sexually Transmitted Infection Positivity Among Substance-Using Native American Adults

Abstract: Background Sexually transmitted infections (STIs) are a public health crisis with Native Americans suffering a high burden of disease. Studies across gender and racial/ethnic groups have found varying risk factors associated with STI positivity. Understanding how risk factors are associated with STI positivity can help design interventions for those most at risk. Methods Participants were Native American binge substance using adults enrolled in a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“… Level of education: The results of some studies showed that there was a significant relationship between educational status and awareness about HIV, concerns about the risk of contracting HIV through unprotected sex, and the lack of sustained use of condoms. [ 22 23 ] Jones et al . [ 10 ] showed that there was a significant relationship between a low level of education and involvement in exchange sex (the exchange of monetary or non-monetary items for sex).…”
Section: Resultsmentioning
confidence: 99%
“… Level of education: The results of some studies showed that there was a significant relationship between educational status and awareness about HIV, concerns about the risk of contracting HIV through unprotected sex, and the lack of sustained use of condoms. [ 22 23 ] Jones et al . [ 10 ] showed that there was a significant relationship between a low level of education and involvement in exchange sex (the exchange of monetary or non-monetary items for sex).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, traumatic life events and stress have been associated with sexual risk behaviors in AI youth and adults. This was especially the case among young women in a study conducted with a Northern Plains tribe (43) and in a study with a Southwestern tribe (7,25).…”
Section: Conceptual Frameworkmentioning
confidence: 89%
“…Alternatively, in Native communities it is important to consider the importance of communal risk; literature specific to Native communities underscores Native cultural practices and values about the importance of family and community for promoting health and wellness (23,24). Thus, we suggest taking a more holistic view of behavior change when working with Native communities which includes utilizing Native-centered theories and including measures such as household size as a proxy measure for social support and family engagement (25). Furthermore, treatment approaches that are congruent with AI/AN cultural values, traditions, and customs enhance treatment engagement (26)(27)(28).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations